Drug rationality profile in diabetes mellitus patients - Shinta Mayasari; Wima Anggitasari; Iski Weni Pebriarti (Sean Institute, 2023)
Diabetes mellitus was a metabolic disease characterized by hyperglycemia that occured due to the inability of the pancreas to secrete insulin, impaired insulin action, or both. According to Riskesdas data (2018), the prevalence of diabetes mellitus in Jember district was in third place. The increased prevalence was caused by one of them, namely the result of inappropriate drug use. The rationality of the drug could be seen from the accuracy of the type of drug, dosages, patient, dosage of each drug. The purpose of this study was to determine the rationality profile of drugs in patients with diabetes mellitus. This type of research was an observational study with a cross-sectional design. The data collection technique used random sampling, with the number of samples in the study being 43 samples. The sample in this study was medical record data of diabetes mellitus patients. The instruments used in the study were patient medical records, hospital formularies and data recapitulation sheets. Data was processed descriptively displayed in the form of frequency and percentage. The results showed that the accuracy of the drug was 95,35%, the accuracy of the dosage was 100%, the accuracy of the patient was 100%, the accuracy of the drug indication was 95,35%, so it was concluded that the rationality of the drug was 97,67%. Drugs were given based on indications, doses, drugs, and patient conditions. Physician provided drug therapy according to hospital procedures that refered to the hospital formulary.